Desarrollo de una guía inteligente que permita conocer los componentes internos de un computador utilizando la realidad aumentada para los alumnos de la carrera de ingeniería en sistemas de la Universidad Nacional de Loja. - Cañar Lalangui, Janeth Alexandra, Maritza Elizabeth Tandazo Bazaran (2016)
At the National University of Loja, the development of an application that allows one to view the international components of a computer using Augmented Reality which shows 3D objects via a mobile device, is very important. It is for this reason that this work aims to develop an application based on Augmented Reality which will aid in both the teaching and learning of systems engineering. In order to create the application, software development methodologies and other tools were used. Thus creating an application called “Intelligent Guide” which shows the student the internal components of the computer, in Augmented Reality, through the use of a mobile phone witch android technology and maker; it also has web page that allows the user to see how thaw application was developed. In order to assess the application, surveys which allowed for the improvement of the application’s functionality and interface were developed. As for the results and discussion, an indication of how one managed to meet the goals and the processes that were necessary to provide a solution to the requirements was given. In addition, the Xp methodology, which we adapted to our needs, was used. With the development of the application “Intelligent Guide”, a tool based on Augmented Reality which allows you to work in an educational context without adding any difficulty level to the user’s learning, has been made known. Moreover one say that the manipulation of the application resulted in motivational experiences for different users.